Odpowiedzi

2009-11-06T16:11:54+01:00
A)x+(-1)[x+(x-1)] dla x= -0,1
x-x-x+1=-x+1
-(-0,1)+1=1,1
b)(2x-3)(x+6)-x(2x²+4x+9) dla x=⅔chyba 2/3?

2x²+12x-3x-18-2x³-4x²-9x=-2x³-2x²-18
Mamy
-2*(2/3)³-2(2/3)²-18=-16/27-8/9-18=-40/27-18=-19 13/27

c)6x(x+x²-x³)-(x+1)(x²+1) dla x= -2
6x²+6x³+6x⁴-(x³+1+x²+1)=6x⁴+5x³+5x²-2
6*(-2)⁴+5*(-2)³+5*4-2=6*16-40+18=56+18=74
2009-11-06T16:41:48+01:00
A)=(-0,1)+(-1)*[(-0,1)+((-0,1)-1)]=-1,1*[(-0,1)+(-1,1)]=-1,1*(-1,2)=1,32
b)=(2*2/3-3)*(2/3+6)-2/3*[2*(2/3)²+4*2/3+9]=(4/3-3)*20/3-2/3*(2*4/9+8/3+9)=-100/3-2/3*(8/9+8/3+9)=-100/3-2/3*(8/9+24/9+81/9)=-100/3-(2/3*113/9)=-100/3-226/27=27-226/27=-1126/27
c)=6*(-2)*[(-2)+(-2)²-(-2)³)-((-2)+1*((-2)²+1)=-12*(-2+4+8)-(-1)*5=-12*10-(-5)=-120+5=-115
d)=(9/4-1)*{3*(9/4+2)-2*(9/4+3)}=(9/4-4/4)*{3*(9/4+8/4)-2*(9/4+12/4)}=5/4*{3*17/4-2*21/4}=5/4*{51/4-42/4}=5/4*9/4=45/16
2009-11-06T18:08:33+01:00
A)x+(-1)[x+(x-1)] dla x= -0,1
x-x-x+1=-x+1
-(-0,1)+1=1,1
b)(2x-3)(x+6)-x(2x²+4x+9) dla x=⅔chyba 2/3?

2x²+12x-3x-18-2x³-4x²-9x=-2x³-2x²-18
Mamy
-2*(2/3)³-2(2/3)²-18=-16/27-8/9-18=-40/27-18=-19 13/27

c)6x(x+x²-x³)-(x+1)(x²+1) dla x= -2
6x²+6x³+6x⁴-(x³+1+x²+1)=6x⁴+5x³+5x²-2
6*(-2)⁴+5*(-2)³+5*4-2=6*16-40+18=56+18=74